Ecosystem sustainability and global change - Monaco, André; Prouzet, Patrick (Oceanography and marine biology series. Seas and oceans set., 2014)
This volume provides various examples and dimensions, chemical, biological, climatic, or related to extreme (hazards). It describes, by reciprocity, the vulnerability of ecosystems, resources, heritage, human health and, consequently, economic and social sectors. it considers climate scenarios and socio-economic status indicators research, design strategies and patterns of adaptation, development of innovative monitoring systems, analysis of perceptions of major hazards and valuation of ecosystem services.